Penerapan E-Learning Dalam Upaya Meningkatkan Kemampuan Komunikasi Matematis Mahasiswa - Supianti, In In (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2014)
The aim of this study is to examine the problem of improving mathematical communication ability of students through the implementation of e-learning in mathematics. The research method in the form of a quasi-experimental study using pretest-posttest design. The population is student of Mathematics Education University of Pasundan, while the second semester student is sample, class A as a control class and class B as a experiment class. The instrument used in this study is 6 numbers of mathematical communication ability test and observation sheet. The results obtained are the improvement of communication skills students acquire mathematical study of mathematics by using e-learning better than students who use conventional learning.